LITHUANIAN CIVIL SERVANTS AT THE EUROPEAN COMMISSION: A LOOK THROUGH THE FRAMEWORK OF DIASPORA NETWORKS - Gineikytė, Vaida (Politologija, 2015)
The article is an initial attempt to analyse the possibility to compensate the brain drain loss of qualified civil servants who left the country for work in the European Union institutions. Emigration of these people has been perceived as an important loss for the Lithuanian public sector. This approach was supported by the traditional human capital paradigm in migration studies which implied that knowledge and experience were inseparable from physical body, and once a person left his home country, the country lost his human capital. However, the new brain drain theories question this premise and state that expatriates can be engaged with the home country and contribute to its development without being there physically via the transfer of information and knowledge. They introduce another option to reverse brain drain besides repatriation – the so-called diaspora option. This approach has so far been applied to study mostly scientists and businessmen, but expatriates working at the European institutions also meet all the criteria to become the object of intellectual diaspora studies. Moreover, the expatriate civil servants gain valuable knowledge that can improve the operation of Lithuanian institutions. Hence, the article aims to elucidate the preconditions of Lithuanian officials’ participation in expatriate knowledge networks and engagement with the development of their home country. The scope of this study was limited to civil servants of the European Commission: this institution is often characterised as an identity-changing organisation with strong supranational values which may imply declining national affiliations of its members. In the study, discoveries of different authors were combined to create a theoretical tool which was invoked to evaluate the engagement with the home country. It took into account the structure of expatriate social networks; their involvement in the home country; motivation to involve stemming from identity and values; and expatriates’ reaction to policies of the home country. Quantitative and qualitative approaches were combined to answer the research question. A survey of Lithuanian officials of the European Commission revealed the general trends, while in-depth interviews helped to contextualise the information related to the Lithuanian networking in Brussels and to better understand the intricate aspects of identity and engagement with the home country. The results have demonstrated that even though the majority of respondents can be characterised by pride in their nationality, national networking and national affiliations, there is a lack of other preconditions for successful transactions with tangible outcomes for the home country. The national networks of Lithuanian civil servants of the European Commission cannot be characterised by the necessary diversity and lack connections with other diaspora organisations; the current character of their engagement with the home country is rather sporadic and small-scale; finally, there is a lack of incentives for a greater involvement from the home country through targeted policy measures.